Evolutionary game analysis of community elderly care service regulation in the context of “Internet +” - Wang, Qiangxiang; Liu, June; Zheng, Yue (Frontiers in Public Health, 2022)
Background As an upgraded form of the elderly care service industry, “Internet + Community Elderly Care” integrates information technology, artificial intelligence, Internet thinking, and the construction of community elderly care service mechanisms. Research on “Internet + Community Elderly Care” has become a focus. Methods The four-party evolutionary game model of elderly service regulations was presented, which consists of the government, providers, platforms, and elderly people. By using Lyapunov stability theory, the stability of each player's strategy selection was analyzed. Furthermore, the sensitivity analysis of the key parameters was discussed in detail using system dynamics. Results and discussion Online evaluations of elderly people have more positive effects on the regulatory system than offline evaluations. Both the penalties on providers and subsidies on platforms given by the government have thresholds. Moreover, government penalties for providers and subsidies for platforms could curb their speculative behavior and enable effective steering of providers and platforms. Conclusion The Omni-feedback mechanism for elderly people can effectively curb the speculative behavior of elderly care service providers and elderly care service information platforms. The government should dynamically adjust penalties and subsidy policies.